Pengembangan media LKS berbasis praktikm untuk meningkatkan minat belajar siswa pada materi ekosistem - Fortuna, Ihza Amalia; Fitri Rizkiyah; Rizqi Nur Rachmawati; Mona Anju Sansena (Universitas Garut, 2024)
This research aims to develop a practicum-based Student Worksheet (LKS) media to enhance students' learning interest in ecosystem material. The study employed Research and Development (R&D) methodology using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The development of this media has been validated by material experts, media experts, and subject teachers as validators. The instruments used included expert validation sheets, teacher and student response questionnaires, as well as a learning interest questionnaire administered before and after the use of the LKS. The validation results indicated that the practicum- based LKS media was in the